Psychosocial Factors Associated with Longevity in the United States: Age Differences between the Old and Oldest-Old in the Health and Retirement Study - Ailshire, Jennifer A. (SAGE-Hindawi Access to Research, 2011)
Recent growth in the number of adults surviving to advanced ages raises questions about the quality of life associated with increased longevity. Psychosocial factors have received relatively little attention in research on quality of life among the oldest-old. This study uses nationally representative data on older US adults to examine how social relationships, feelings of loneliness, and satisfaction with life and the aging experience differ between the oldest-old, those who have survived to age 90 or older, and older adults in their 70s. We find that the oldest-old are able to maintain social relationships with family and friends and receive more social support than younger elderly adults. Yet, the oldest-old are more likely to feel lonely due to their greater rates of widowhood. Satisfaction with life was higher among the oldest-old, but the oldest-old had more negative perceptions of the aging experience. Psychosocial dimensions of longevity should be considered in research on quality of life among the oldest-old.